Komunikasi Pariwisata dalam Pengembangan Destinasi Wisata Premium Berbasis Pemberdayaan Masyarakat di Labuan Bajo - Henny Lestari Lusiana Lada (CV. Creative Tugu Pena, 2024)
Labuan Bajo is a tourist destination that is already known internationally. The uniqueness of Labuan Bajo lies in its natural panorama and marine tourism. This makes Labuan Bajo a super priority destination for the development of Indonesian tourism. Tourism development includes attractions, accessibility, amenities, and supporters. Labuan Bajo is still faced with obstacles related to the development of the four components of tourism products, so that the tourism potential has not been optimally developed. The purpose of this study is to determine the tourism potential in Labuan Bajo, and Community Empowerment in Labuan Bajo. The method of this writing is a literature review, namely the process of collecting, analyzing, and evaluating relevant written sources such as books, journals, research reports, and other scientific works. In conclusion, tourism communication plays an important role in the development of Labuan Bajo as a premium tourist destination based on community empowerment. This development has a positive impact in the form of increasing the local economy, infrastructure, and cultural preservation, but still faces challenges such as gaps in community skills and threats to environmental sustainability.